2020
DOI: 10.1177/0300060519889718
|View full text |Cite
|
Sign up to set email alerts
|

Application of fast-track surgery combined with a clinical nursing pathway in the rehabilitation of patients undergoing total hip arthroplasty

Abstract: Objective: To explore the effect of fast-track surgery combined with a clinical nursing pathway in the rehabilitation of patients treated with total hip arthroplasty (THA). Methods: We enrolled 70 patients diagnosed with avascular necrosis who were treated with a THA. All patients were randomly divided into either a control or a study group. The control group received routine nursing during the perioperative period while the study group received a fast-track surgery combined with a clinical nursing pathway. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 27 publications
0
19
0
4
Order By: Relevance
“…Patient-reported outcome after fast-track hip arthroplasty measured with the Harris Hip Score (HHS) showed significant improvement (54.0 vs 74.4) comparing preoperatively and four weeks after surgery. Fast-track surgery (56.20 vs 95.36) combined with a clinical nursing pathway can significantly improve the patient-reported and functional outcome of patients undergoing THA (58.09 vs 89.39) measured with Harris Hip Score before surgery and 3 weeks after [ 41 ]. In addition, Maempel et al.…”
Section: Discussionmentioning
confidence: 99%
“…Patient-reported outcome after fast-track hip arthroplasty measured with the Harris Hip Score (HHS) showed significant improvement (54.0 vs 74.4) comparing preoperatively and four weeks after surgery. Fast-track surgery (56.20 vs 95.36) combined with a clinical nursing pathway can significantly improve the patient-reported and functional outcome of patients undergoing THA (58.09 vs 89.39) measured with Harris Hip Score before surgery and 3 weeks after [ 41 ]. In addition, Maempel et al.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, no case of intestinal obstruction was observed. Some scholars reported that the incidence of acute colonic pseudoobstruction after hip and knee replacement was 1.3% and 0.65%, respectively [12][13][14][15]. Postoperative bowel Arthroscopic minimally invasive surgery is a surgery performed using an arthroscope and its related instruments, which is an important part of modern surgery.…”
Section: Discussionmentioning
confidence: 99%
“…One randomized controlled trial was identified, which showed no statistically significant difference in the incidence of deep venous thrombosis (DVT) between the ERAS and control group in patients undergoing THA for osteonecrosis 518 . However, the quality of this evidence was determined to be low due to the lack of a defined randomization process, allocation concealment, and the procedure for identification and diagnosis of DVT, with no blinding of assessors.…”
Section: Arielmentioning
confidence: 99%